(untitled) (American Journal of Islam and Society, 2013)
This lucid and concise book is an important and timely contribution in light of current intra-Muslim political rivalries that find their fueling justifications in the domain of “excommunication” and mutual accusations of disbelief and apostasy (takfīr). This situation has caused Alalwani, the author of this “treatise,” to delve into the controversies and subtleties of this sensitive and manipulation-laden issue. He attempts, both scripturally and logically, to clarify its various aspects and challenge the conventional and traditional approaches to it, which have been obscured by the historical weight of dogma and power politics (pp. 19-20, 129). Alalwani’s contends that there is no explicitly stated evidence, whether from the Qur’an or the Prophet’s Sunnah, that mandates the death penalty for merely changing one’s religion, as long as doing so is not accompanied or associated with another criminal act. He highlights that when stipulating that an apostate should be killed, the jurists were in fact dealing with “compound” crimes that involved, in addition to apostasy, other political, legal, and social dimensions (p. 1). He proceeds to make his point by providing evidence from the Qur’an and the Sunnah while casting doubt on the authenticity or consistency of much of what the fuqahā’ (jurists and scholars) narrated later on and attributed to the Prophet or his Companions. His chosen method combines philosophical, analytical, inductive, and historical approaches along with Islamic textual sciences and fields of knowledge (p. 3). He focuses on cases in which an individual changes his/her faith without engaging in hostile or criminal activities against the Muslim community, which otherwise would elevate the case to one of security threat or treason (p. 4). The study comprises six chapters. The first two deal with whether apostasy is a capital crime and with the Qur’anic depiction of what apostasy means. Alalwani points out that despite unleashing the “sword of consensus” regarding the death penalty for this event, in fact there is no such consensus, for no ...